Designing a quality improvement intervention: a systematic approach. Issue 3 (1st June 2003) - van Bokhoven, M A; Kok, G; van der Weijden, T
Abstract : Most quality improvement or change management interventions are currently designed intuitively and their results are often disappointing. While improving the effectiveness of interventions requires systematic development, no specific methodology for composing intervention strategies and programmes is available. This paper describes the methodology of systematically designing quality of care improvement interventions, including problem analysis, intervention design and pretests. Several theories on quality improvement and change management are integrated and valuable materials from health promotion are added. One method of health promotion—intervention mapping—is introduced and applied. It describes the translation of knowledge about barriers to and facilitators of change into a concrete intervention programme. Systematic development of interventions, although time consuming, appears to be worthwhile. Decisions that have to be made during the design process of a quality improvement intervention are visualised, allowing them to serve as a starting point for a systematic evaluation of the intervention.